Constructing a 'great' role for Britain in an age of austerity: interpreting coalition foreign policy, 2010-2015 - Daddow, O. (SAGE Publications, 2015)
This article interprets the ideational underpinnings of the British Conservative–Liberal coalition government’s foreign policy from 2010 to 2015. It uses qualitative discourse analysis of speeches, statements and policy documents to unpack the traditions of foreign policy thought which informed some of the key foreign policy practices of the coalition government. The analysis centres on the British identity constructed by liberal Conservatives, and the values and interests flowing from this baseline identity that the government’s foreign policy sought to express through its foreign policy. Liberal Conservative foreign policy is argued to have been an attempt to come to terms with the limits on Britain’s international agency in the face of three major foreign policy dilemmas: the legacy of the New Labour years, dramatically reduced economic resources in the ‘age of austerity’ and an increasingly restricted capacity for Britain to exercise ideational entrepreneurship in the international community. The article substantiates the claim in the extant literature that liberal Conservatism significantly adapted but did not restructure an established British foreign policy tradition of merging values and interests in complex ways.